Genome-Wide Association Study of Body Weight Traits in Inner Mongolia Cashmere Goats - Zhang, Lei; Wang, Fenghong; Gao, Gong; Yan, Xiaochun; Liu, Hongfu; Liu, Zhihong; Wang, Zhixin; He, Libing; Lv, Qi; Wang, Zhiying; Wang, Ruijun; Zhang, Yanjun; et al. (Frontiers in Veterinary Science, 2021)
Objective: Body weight is an important economic trait for goat, which greatly affects animal growth and survival. The purpose of this study was to identify gene-associated to Birth Weight (BW), Weaning Weight (WW), and Yearling Weight (YW). Materials and Methods: In this study, genome-wide association study of Birth Weight (BW), Weaning Weight (WW), and Yearling Weight (YW) were determined using the GGP_Goat_70K SNP chip in 1920 Inner Mongolia cashmere goats. Results: We discovered that 21 single nucleotide polymorphisms (SNPs) were significantly associated with BW on the genome-wide levels. These SNPs were located in 10 genes, e.g. MAPK3、LDB2 and LRP1B, which may be related to muscle growth and development in Inner Mongolia Cashmere goat. Gene Ontology and KEGG enrichment analysis revealed that these genes were significantly enriched in Regulation of actin cytoskeleton and Phospholipase D signaling pathway etc. Conclusion: In summary, this study will improve the marker assisted breeding of Inner Mongolia cashmere goats, as well as the molecular mechanisms of important economics traits.